Perspectives of Technical Assistance Providers on Nature-Based Solution Practices in North Carolina, USA - Courtney B. Deviney; Rajan Parajuli; Frederick W. Cubbage; Erin O. Sills; Robert E. Bardon; Stephanie Chizmar; Kathleen McGinley (Environmental Management, 2026)
Nature-based solutions (NBS) are increasingly promoted in agricultural and forestry policy, yet their effectiveness depends on technical assistance providers (TAPs) who translate policy guidelines into land management decisions. Drawing on Diffusion of Innovations and Value–Belief–Norm frameworks, this study examines how TAPs’ professional backgrounds, organizational affiliations, regional contexts, and management experiences shape their knowledge, perceived importance, and promotion of NBS. A web-based survey of 101 TAPs in North Carolina was analyzed using Spearman correlations and logistic regression. While 79% of respondents reported familiarity with NBS, only about half of them actively promoted these practices. Adoption pathways varied across sectors. In agriculture, recent management experience was linked to greater emphasis on ecosystem services and higher likelihood of promoting NBS. In forestry, engagement was stronger for establishment and periodic management practices than for timber-oriented activities. These findings highlight the need for sector-specific outreach strategies that account for TAPs’ professional contexts and institutional settings to improve NBS adoption on working lands.

Characterizing Community Forests in the United States - Reem Hajjar; Kathleen McGinley; Susan Charnley; Gregory E Frey; Meredith Hovis; Frederick W Cubbage; John Schelhas; Kailey Kornhauser (Journal of Forestry, 2024)
Research on community forests (CFs), primarily governed and managed by local forest users in the United States, is limited, despite their growth in numbers over the past decade. We conducted a survey to inventory CFs in the United States and better understand their ownership and governance structures, management objectives, benefits, and financing. The ninety-eight CFs in our inventory are on private, public, and tribal lands. They had various ways of soliciting input from, or sharing decision-making authority with, local groups, organizations, and citizens. Recreation and environmental services were the most important management goals, but timber production occurred on more than two-thirds of CFs, contributing to income on many CFs, along with a diversity of other income sources to fund operations. We discuss the difficulties in creating a comprehensive CF inventory and typology given the diversity of models that exist, reflecting local social and environmental conditions and the bottom-up nature of community forestry in the United States. Study Implications: Despite their small footprint in the United States, community forests are a rapidly developing model of forest ownership, governance, and management that helps protect forestlands and open space and demonstrates how market and nonmarket forest goods and services can be produced for broad and enduring community benefits. This study inventories and characterizes community forests in the United States to increase understanding of this model, its prevalence, and its potential. It provides a baseline of information that serves as a foundation for further exploration and research on the impacts and contributions of community forests.

Corrigendum to: Forest Sector Research and Development Capacity - Kathleen A Mcginley; Richard W Guldin; Frederick W Cubbage (Journal of Forestry, 2021)

Projecting global and regional outlooks for planted forests under the shared socio-economic pathways - Jaana Korhonen; Prakash Nepal; Jeffrey P. Prestemon; Frederick W. Cubbage (New Forests, 2021)
There is rising global interest in growing more trees in order to meet growing population, climate change, and wood energy needs. Using recently published data on planted forests by country, we estimated relationships between per capita income and planted forest area that are useful for understanding prospective planted forest area futures through 2100 under various United Nations Intergovernmental Panel on Climate Change-inspired Shared Socio-economic Pathways (SSPs). Under all SSPs, projections indicate increasing global planted forest area trends for the next three to four decades and declining trends thereafter, commensurate with the quadratic functions employed. Our projections indicate somewhat less total future planted forest area than prior linear forecasts. Compared to 293 million ha (Mha) of planted forests globally in 2015, SSP5 (a vision of a wealthier world) projects the largest increase (to 334 Mha, a 14% gain) by 2055, followed by SSP2 (a continuation of historical socio-economic trends, to 327 Mha, or an 11% gain), and SSP3 (a vision of a poorer world, to 319 Mha, a 9% gain). The projected trends for major world regions differ from global trends, consistent with differing socio-economic development trajectories in those regions. Our projections based on empirical FAO data for the past 25 years, as well as those by other researchers, suggest that achieving the much more ambitious global planted forest targets proposed recently will require exceptional forest land and investment supply shifts.

Structural Changes on Pulpwood Market in the US South: Wood Pellets Investments and Price Dynamics - Bruno Kanieski da Silva; Frederick W Cubbage; Robert C Abt (Forest Science, 2019)
We investigated the impact of wood pellet mills on pulpwood price structure in the US South. Rather than focusing exclusively on price elasticities, we progress by examining how wood pellet production has affected the spatial transmission of pulpwood prices. Pairwise price ratios were modeled using smooth transition regression to identify changes in the cointegration (linkage) between markets over time. A logistic model was fitted to estimate market linkages as a function of market distances, industry concentration, and capacity of pellet wood production. Results show that the US South is not composed of market clusters, but each market pair has a particular relation. Distance and wood pellet production capacity are the only factors driving market linkages; the pulp and paper industries did not affect market structure changes. Our research suggests spatial price transmission varies over time, and pellet mills have caused a structural change in the pulpwood prices in the US South.

Forest Sector Research and Development Capacity - Kathleen A McGinley; Richard W Guldin; Frederick W Cubbage (Journal of Forestry, 2019)
Current trends in the nation’s forest-sector research capacity were analyzed in terms of funding and number of scientists, and compared with prior data in the National Research Council’s 2002 report, National Capacity in Forestry Research. The total number of professors at institutions with academic programs accredited by the Society of American Foresters, research scientists at the USDA Forest Service, and forest researchers in forest industry decreased approximately 12 percent since 2002. In 2016, there were an estimated 1,224 professors and 540 Forest Service research scientists, for a total of 1,764 scientists. Total estimated research funding in 2015 for universities, private sector, and USDA Forest Service, including appropriations from federal grant programs from the USDA National Institute for Food and Agriculture, National Science Foundation, National Aeronautics and Space Administration, and Department of Energy was US$598 million—a nominal increase over 2002, but a decrease when accounting for inflation. The proportion of reported scientists’ disciplines shifted notably from production subjects to broader ecosystem services and forest health subjects, as well as from more applied to more fundamental or basic research. The data indicated that the nation’s forest research capacity continues to erode, leading to declines in research development and innovation, and putting at increasing risk the future health and productivity of America’s forests.

Modeling the Financial Potential of Silvopasture Agroforestry in Eastern North Carolina and Northeastern Oregon - Sonia R Bruck; Badege Bishaw; Tamara L Cushing; Frederick W Cubbage (Journal of Forestry, 2019)
Silvopasture is the planned and managed agroecosystem in which forage, livestock, and woody perennials are integrated “either simultaneously or sequentially on the same parcel of land.” Silvopasture can help mitigate anthropogenic climate change through carbon sequestration in perennial vegetation. We examined silvopasture, forest, and pasture systems in eastern North Carolina and northeastern Oregon. In North Carolina, we evaluated forest and agroforestry systems using loblolly and longleaf pine species. In Oregon, we evaluated forest and agroforestry systems using ponderosa pine. We based the analyses on typical forest and cattle regimes, including yields, costs, and prices obtained from the literature, and consulted with experts in the respective subjects. The financial viability of land management investments was investigated using capital budgeting techniques. Cash flows were developed using 4 percent and 6 percent real discount rates. Analysis suggests loblolly pine timber management and cattle management are more profitable than silvopasture management in eastern North Carolina. Additionally, cattle management is more profitable than silvopasture in northeastern Oregon. Longleaf pine and ponderosa pine are not profitable when solely managed for timber and can benefit financially when combined with livestock.

Current Perspectives on Sustainable Forest Management: North America - Jacek P. Siry; Frederick W. Cubbage; Kevin M. Potter; Kathleen McGinley (Current Forestry Reports, 2018)

Greenhouse gas emissions in an agroforestry system of the southeastern USA - Alan J. Franzluebbers; Janet C. Chappell; Wei Shi; Frederick W. Cubbage (Nutrient Cycling in Agroecosystems, 2017)

A Watershed-Scale Model for Predicting Nonpoint Pollution Risk in North Carolina - Kevin M. Potter; Frederick W. Cubbage; Gary B. Blank; Rex H. Schaberg (Environmental Management, 2004)

Employment and Education in Forestry: National Perspectives, North Carolina Trends - Frederick W. Cubbage; Larry G. Jervis; P. Gregory Smith (Journal of Forestry, 1999)
A comparison of data on the first jobs of one university's forestry graduates with national data on members of the foresters' professional association points to some trends in forestry employment. Compared with older alumni and with Society of American Foresters members as a whole, recent graduates from North Carolina State University are taking fewer positions with federal agencies and in land management, but more consulting jobs and specialized procurement or environmental services positions. Graduates with advanced degrees are finding more career opportunities than bachelor's-degree foresters. To prepare their graduates for future employment, forestry education programs need to reflect regional differences in employment.

Using multiple objective linear programming to evaluate multi-participant agroforestry systems - Paul A. Wojtkowski; Graham H. Brister; Frederick W. Cubbage (Agroforestry Systems, 1988)